Assessing the Impact of Nano-Graphene Oxide Addition on Surface Microhardness and Roughness of Glass Ionomer Cements: A Laboratory Study - Farahnaz Sharafeddin; Mohammad Mahdi Shirani; Zahra Jowkar (International Journal of Dentistry)
Background. Nanomaterials, including nano-graphene oxide (nGO), have emerged as promising modifiers for dental materials. Therefore, this study investigated the effect of incorporating nGO into conventional glass ionomer cement (CGIC) and resin-modified glass ionomer cement (RMGIC) on surface roughness and hardness. Methods. Sixty disk-shaped specimens (2 × 6 mm) were divided into six groups: CGIC, RMGIC, CGIC with 1 wt.% nGO, CGIC with 2 wt.% nGO, RMGIC with 1 wt.% nGO, and RMGIC with 2 wt.% nGO. Surface roughness (Ra) and Vickers microhardness (VHN) were measured using a surface profilometer and Vickers microhardness tester, respectively. Statistical analysis employed the Kruskal–Wallis and Mann–Whitney tests (p <0.05). Results. The microhardness of RMGICs significantly increased with 1% and 2% nGO (p=0.017, P=0.001, respectively), while CGICs showed a significant decrease in VHN with nGO incorporation (p=0.001). VHN values of all CGIC groups were significantly higher than those of all RMGIC groups (p=0.001). Mean surface roughness values for all CGICs were significantly higher than those of RMGIC groups (p=0.001). Within the RMGIC groups, mean Ra values of RMGIC + 1 wt.% nGO and RMGIC + 2 wt.% nGO groups decreased significantly compared to the RMGIC control group (p=0.001, p=0.001, respectively). Among CGIC groups, mean Ra values of 1 wt.% and 2 wt.% nGO/CGIC groups were significantly higher than the CGIC control group (p=0.016, p=0.001). Conclusion. Incorporating nGO into RMGICs increased surface microhardness while reducing surface roughness, offering potential advantages for clinical applications. Conversely, adding nGO to CGICs increased surface roughness and decreased surface hardness. These findings emphasize the potential benefits of utilizing nGO in RMGICs and their implications in clinical practice.